RI 6220 Synthesis Of Fibrous Silicon Carbide By Thermal Reduction Of Silicates And Silicon Compounds - John K. Alley (The National Institute for Occupational Safety and Health (NIOSH), 1963)
Fibrous silicon carbide was produced by thermal decomposition of certain silicates contained in graphite crucibles. Induction heating was used to produce the necessary temperature and thermal gradients. Both green and white fibers were mainly the beta modification even though each color grew within a different temperature zone. Alpha silicon carbide, present in insufficient amounts for X-ray detection, was identified by electron diffraction. The white fibers formed in a zone between 1,365° and 1,634° C (±50° C). The green fibers (less contaminated) formed in a much more narrow zone between 1,650° and 1,672° C (±50° C). The average lengths and widths of microscopic fibers grown by this method were 1.5 mm/0.002 mm (white) and 1.2 mm/0.0035 mm (green); however, same fibers observed by electron microscope had cross-sectional measurements of 150 to 300 A. Both differential thermal analysis and thermogravimetric analysis showed that silicon carbide fibers oxidized in air at temperatures above 500° C. Fibrous silicon carbide was indexed as a cubic cell with the dimensions a = 4.358 A. The density calculated from X-ray data was 3.217 g/cm3.